Structural methods in molecular inorganic chemistry - Rankin, David W. H. (John Wiley & Sons, Inc., 2013)
"Structural Methods in Molecular Inorganic Chemistry is designed to help readers interpret experimental data, understand the material published in modern journals of inorganic chemistry, and make decisions about what techniques will be the most useful in solving particular structural problems"--